Pemanfaatan Kompos Kiambang dan Sabut Kelapa Sawit sebagai Media Tanam Alternatif pada Prenursery Kelapa Sawit (Elaeis guineensis Jacq.) - Adryade Reshi Gusta; Any Kusumastuti; Yonathan Parapasan (Jurnal Penelitian Pertanian Terapan, 2015)
The efforts to achieve optimal results in the development of oil palm cultivation one of which is the use of the planting medium. Palm oil seedlings require planting medium that has the chemical and physical properties are good. Media palm nurseries generally consist of topsoil are mixed with sand and organic matter which is expected to obtain a good medium fertility premises. Top soil needs more difficult, so we need to look for alternative media to growing media prenursery palm oil. This study used randomized complete design and experiment arranged in seven media with four replications. The applications method of media: 100 % topsoil (A), topsoil and salvinia compost (1:1) (B), topsoil and coir palm oil (1:1) (C), topsoil and salvinia compost (1:2) (D) , topsoil and coir palm oil (1:2) (E), coir palm oil and salvinia compost (1:2) (F) , topsoil , salvinia compost, and coir palm oil (1:1:1) (G). All data were analyzed for variance. Data analysis followed by separation of means using LSD test with significance level of 5%. The resulted showed that both time and applications method of topsoil have affect on growth component. The best application method was topsoil, salvinia compost, and coir palm oil increased dry weight and root dry weight. Keywords: Prenursey, topsoil , salvinia compost, coir palm oil